Size-TunableMesoporous Silica for Macromolecular Drug Delivery. (March 2019) - Wang, Yiyu; Niu, Chunqing; Gu, Jiamin; Hu, Chao; Wang, Youning; Zhang, Junhua
Abstract: A series of mesoporous silica nanospheres(MSNs)and different particle sizes rangingfrom about48 to 215nm has been successfully synthesized through modified base-catalyzed sol-gel method. The particle size distribution, structural and morphological of the samples were well characterized by dynamic light scattering technique (DLS), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and thermalgravimetry (TG). The results reveal that this MSNs exhibits good physicalproperties, including narrow size distribution, uniform pore texture in the nanospheres and good thermal stability. What's more, the size canbetuned by altering the concentration of aqueous ammonia in the silica precursor systems. The obtained MSNs are further used as a drug delivery carrier toinvestigate the in vitro drug release properties usingbovine serum albumin (BSA) as a macromolecularrepresentative model drug. It is found that this MSNsexhibit good obvious sustained release properties for macromolecular drug, suggesting its potential application in biological fields.